SPECIAL EDUCATION SERVICE FOR TALENTED CHILDREN ON SPORT - Fauzi Fauzi (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2016)
This article aims to reveal the education service development for talented children on sport. Talented on sport means students who have high potential to developed to be an athlete who able to achieve high achievement. Nowadays, Sport fostering through elementary and junior high school way is not fully paying attention and giving special education service yet for talented children.Recent in Indonesia, special school for sport is has been developed such as Ragunan school, but that school has not able to retain and give service for talented children yet. Moreover; the · innovation which has to develop in giving special education service is through school sport club model, inclusion class, sport class and special school for sport. In this article, it will be discussed about juridical base, curriculum, organization prin ciple, empower and others. If those applied professionally, the Indonesian's achievement will be glorious again. Keywords: development, service, talent, sport